ReviewINTENSE PHYSICAL EXERCISE RELATED TO THE EMERGENT GENERATION OF CARDIO- VASCULAR RISK MARKERS: A REVIEW - Le Goff, C.; Laurent, T.; Kaux, J.F.; Chapelle, J.P (Biology of Sport, 2012)
Objective: The present review was performed in order to bring together the current knowledge about the impact of intense physical exercise on cardiovascular function, especially on plasma levels of cardiovascular risk markers such as cardiac troponin T (cTnT), myeloperoxidase (MPO), amino-terminal pro-brain natriuretic peptide (NT-proBNP), C-reactive protein (CRP) and oxidized low-density lipoprotein (oxLDL). Methods: Data were collected using the PubMed database. The articles were chosen for their relevance and importance in the area of interest. Results: The literature describes numerous examples where physical exercise induces plasma variation for the markers studied. Intense physical effort increases the levels of cTnT, MPO and NT proBNP whereas CRP, and oxLDL levels tend to be decreased with regular sport activities. Conclusions: The present literature investigation confirms the fact that intense physical exercise has an impact on the plasma variations of the five cardiovascular risk markers studied. However, practising regular exercise remains one of the first strategies for the prevention of cardiovascular disorders.